Balita Stunting di Desa Kedalon : Studi Deskriptif - Fibrinika Tuta Setiani; Heni Lestari; Abdullah Azam Mustajab (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Stunting as a condition of malnutrition with potentially irreversible results due to poor nutritional intake. The negative impacts caused by stunting include impaired brain development, decreased intelligence, impaired physical growth and body metabolism. The purpose of the study was to examine the incidence of stunted toddlers in Kedalon Village, Kalikajar District, Wonosobo Regency. The research method used descriptive analytical observation by conducting secondary data observation of the results of height measurements in Kedalon Village, a population of 193 toddlers was obtained and a sample of 10 toddlers who experienced stunting and the data was analyzed using descriptive. The results of the study showed that the height of stunted toddlers was the highest in the very short category of 6 (60%) and short as many as 4 (40%) toddlers, there were 10 stunted toddlers.